Incidence, etiology, risk factors, and outcomes of pre‐engraftment bloodstream infections after first and second allogeneic hematopoietic cell transplantation. Issue 3 (9th May 2022) - Akhmedov, Mobil; Klyasova, Galina; Kuzmina, Larisa; Fedorova, Anastasia; Vasilyeva, Vera; Drokov, Mikhail; Parovichnikova, Elena
Abstract: Introduction: With an increasing number of allogeneic hematopoietic cell transplantations (allo‐HCT) bloodstream infections (BSI) are still among the most common and serious complications. This study aimed to analyze the incidence, etiology, risk factors, and outcomes of pre‐engraftment BSI after the first and the second allo‐HCT. Materials and methods: This is a retrospective study of 284 patients who underwent the first allo‐HCT and 37 patients after the second allo‐HCT at the National Research Center for Hematology in Moscow, Russia, from January 2018 till September 2021. Results: Cumulative incidence of pre‐engraftment BSI was 29.9% after the first allo‐HCT and 35.1% after the second ( p = .805). The median time to the first BSI was 9 days (range 0–61 days) after the first and 16 days (range 1–28 days) after the second allo‐HCT ( p = .014). A total of 113 pathogens were isolated during 94 BSI episodes after the first allo‐HCT (gram‐negative bacteria 52.2%; gram‐positive bacteria 47.7%). Fourteen pathogens were isolated during 14 BSI episodes after the second allo‐HCT (gram‐negative bacteria 50.0%; gram‐positive bacteria 50.0%). The only significant difference was found in the rate of carbapenem‐resistant gram‐negative bacteria, which was higher after the second allo‐HCT compared to the first (57.1% vs. 13.6%; p = .048). Mismatched unrelated donor (hazards ratio [HR] 3.01; 95% confidence interval [CI]: 1.62–5.60; p < .0001) and haploidentical donor transplantations (HR 1.84; 95% CI: 1.02–3.33; p = .042) were the only independent risk factors associated with the higher risk of pre‐engraftment BSI. Overall 30‐day survival after all BSI episodes was 94.4%. Survival was lower after BSI during the second allo‐HCT compared to the first (71.4% vs. 97.9%; p < .0001), particularly after BSI was caused by carbapenem‐resistant gram‐negative bacteria (25.0% vs. 100.0%; p = .0023). The non‐relapse mortality rate at day +60 was 4.0%, and the risk was highly associated with primary graft failure (HR 9.62; 95% CI: 1.33–71.43), second allo‐HCT (HR 6.80; 95% CI: 1.36–34.48), and pre‐engraftment BSI caused by carbapenem‐resistant gram‐negative bacteria (HR 32.11; 95% CI: 4.91–210.15). Conclusions: Pre‐engraftment BSI is still a common complication after allo‐HCT, particularly after mismatched unrelated and haploidentical donor transplantations. BSI incidence was slightly higher after the second allo‐HCT with a significantly higher rate of carbapenem‐resistant BSI. Although pre‐engraftment BSI would generally follow a benign clinical course, survival was dramatically lower during the second allo‐HCT, especially after carbapenem‐resistant BSI.